ANALISIS KELAYAKAN FINANSIAL BUDIDAYA INTENSIF TANAMAN PALA DI KECAMATAN GISTING KABUPATEN TANGGAMUS - Dwi Apriliansyah Astanu; R Hanung Ismono; Novi Rosanti (Lampung University, 2013)
The purposes of this research are to analyze the financial feasibility of nutmeg farming and the feasibility of its cultivation aspects, technical aspects, and market aspects. This research uses a census method. Feasibility analysis is calculated by the ratio of revenue to cost (B/C), Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), sensitivity analysis, and analysis the feasibility of cultivation aspects, technical aspects, and market aspects. The results showed that at 15% of interest rate, the 25 years long of intensive cultivation of nutmeg farming in Gisting of Tanggamus Regency deserved Net B/C Ratio 2.23; NPV of Rp125,574,036; IRR 20.98% and PP 10.01. The effect of changes with the likely costsrose by 10%, decreased the production by 25%, or it decreased the output prices by 10%, but the farm was still in the state of intensive nutmeg feasible and profitable. On the cultivation aspects, the climate and rain fall in the district of Gisting Tanggamus was appropriated to nutmeg plants; on the technical aspects, the majority of farmers still used traditional technology, particularly in post harvest technology such as processing of nutmeg became essential oils or a variety of snacks. In fact, on the aspects of the market of nutmeg was very good, in which the demand side was greater than the supply side so that the market opportunity for this product was still very promising. Keywords : B/C, IRR, NPV, PP, nutmeg